Sosialisasi Pencegahan Perilaku Bullying melalui pendekatan Nilai-nilai Islam di SDN Cakru 04 Kab Jember - ., Rusdiyanto; Agus Setiawan, Bahar; Tamami, Badrut (Al-Khidmah Jurnal Pengabdian Masyarakat, 2024)
Based on KPAI's findings, throughout 2021 there were at least 17 cases of bullying in schools, from elementary schools to high schools. This community service method uses an outreach method to partners, namely at SDN Cakru 04, Kencong Jombang District, regarding bullying prevention through several stages. These included a survey of the location of service partners, outreach to students, the Teacher Council and student guardians and the program approach, then this activity was assisted by campus students teaching 6 MBKM Dikti 2023 programs located at SDN 04 Cakru, Kencong District, Jember Regency, totaling 5 students. The task of students is to provide outreach to students and parents regarding bullying prevention. This activity will be carried out for 4 months starting from 4 August 2023 to 4 December 2023. Community service activities include; first, building an Anti-Bullying Culture paradigm in Islam. Second, socialization to parents about good parenting patterns by arranging playing hours and study hours. Third, the Religious Program Approach includes Duha prayers, commemoration of holidays, reading Asmaul Husna.